Innovative leadership of school administrators in network group 15 under the department of education, Bangkok metropolitan administration - รุ่งแสง, ธนพร; ปุญญาธนรัตนะ, ธันยวนันฐ์; บุนนาค, ลลิต (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purpose of this research was to study and compare teachers’ perceptions of the innovative leadership of school administrators in Network Group 15 under the Education Department of the Bangkok Metropolitan Administration, classified by gender, age, and educational level. The sample used in this study consisted of 201 teachers from schools in Network Group 15 under the Bangkok Metropolitan Administration in the academic year 2025. The research instrument was a questionnaire with a five-point rating scale. All items met the required criteria, with Index of Item–Objective Congruence (IOC) values ranging from 0.80-1. The reliability of the questionnaire, determined using Cronbach’s alpha coefficient, was .98. The statistics used for data analysis included mean, standard deviation (S.D.), Independent Samples t-test, and One-way Analysis of Variance (One-way ANOVA). When statistically significant differences were found, pairwise comparisons were conducted using Scheffé’s method.           The research findings were as follows:• Teachers’ perceptions of the innovative leadership of school administrators in Network Group 15 under the Education Department of the Bangkok Metropolitan Administration, both overall and in each aspect, were at the highest level. The aspect with the highest mean score was the creation of an atmosphere and culture conducive to learning, followed by vision for change. The aspect with the lowest mean score was innovative creativity. However, all aspects were rated at the highest level.• Teachers’ perceptions of the innovative leadership of school administrators in Network Group 15 under the Education Department of the Bangkok Metropolitan Administration, when classified by gender, age, and educational level, showed statistically significant differences at the .05 level.